Design and operation of thickened tailings disposal system at Les Mines Selbaie - K. R. Wood; G. W. McDonald (Canadian Institute of Mining, Metallurgy and Petroleum, 1986)
"The tailings disposal system at Les Mines Selbaie includes dewatering of tailings in a high-capacity thickener, followed by point discharge of the thickened solids to form a stable conical pile. Tailings water drains to ponds formed behind engineered dams, prior to either recycling f or process use or discharge to the environment. Design and economic considerations of the system are discussed. Construction, start-up and operating experiences are also presented.Introduction Les Mines Selbaie is located in the Abitibi region of northwestern Quebec, approximately 700 km north of Toronto and 150km south of James Bay. More locally, the Detour gold mine is 60 km to the west while the Noranda smelter is 220 km to the south.The deposit was discovered as a result of a Questor INPUT Mark VI geophysical survey in 1973, followed by diamond drill programs from 1974 to 1976. Three mineralized zones were delineated and underground exploration was carried out on all three. A production decision for the 'B-zone' copper-gold-silver orebody was made in July 1979. The underground operation started in July 1981, with full production of 1500 t/d being achieved in May 1982.During the planning phase, every effort was made to ensure that the operation would be environmentally sound . The design included the provisions of the then newly proposed provincial environmental guidelines. The tailings disposal system formed the most significant part of the environmental program due to the large volumes of solids and water effluent. In addition, the design allowed for future expansion of the system to accommodate mining of the other zones, thus minimizing future costs and disruptions."